Uniqueness of Markov equilibrium in stochastic OLG models with nonclassical production - Marten Hillebrand (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2012)
This paper studies Markov Equilibria (ME) corresponding to recursive equilibria on natural state space in the stochastic OLG model extended to include non-additive utility, nonclassical production, and Markovian production shocks. Specifically, we provide sufficient conditions under which the ME in unique. It turns out that uniqueness for a large class of economies and that restrictions either on the consumption side or the production side alone are sufficient to garantuee this result. We also discuss additional properties such as continuity or smoothness of the equilibrium mappings and whether additional recursive or non-recursive euilibria exist.
urn:nbn:de:swb:90-311289
Keywords: C62; D51; E32; 330; Markov equilibrium : Uniqueness; Overlapping generations; Nonclassical production; Markovian production shocks